Sovereignty as a Bargaining Chip: Organized Hypocrisy in The Modernization of Pituffik Space Base - Putri Alyaa Safira; Wishnu Mahendra Wiswayana (ARRUS Journal of Social Sciences and Humanities, 2026)
This study analyzed the strategic modernization of Pituffik Space Base within the context of deteriorating Arctic geopolitics and the emergence of hypersonic threats. Utilizing Stephen Krasner’s framework of Organized Hypocrisy, the research examined the contradiction between the formal recognition of Danish sovereignty and the actual strategic behavior of the United States between 2020-2026. A qualitative analysis of defense agreements, diplomatic documents, and infrastructure projects was conducted to identify discrepancies between stated norms and operational realities. The results demonstrated that the United States maintained de jure sovereignty through symbolic acts, such as renaming the facility, while simultaneously executing unilateral military expansion and political intervention. The findings indicated that this decoupling allowed for a sovereignty of permissions, where the host nation retained legal title while the external power secured total operational access. The study concluded that this arrangement minimized transaction costs for the great power while preserving the diplomatic legitimacy of the semi-sovereign territory.